2012
DOI: 10.1038/pj.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon fiber on the capillary extrusion behaviors of high-density polyethylene

Abstract: The capillary extrusion behaviors of high-density polyethylene (PE) containing carbon fibers (CF) were investigated from a viewpoint of their rheological properties. For values of CF content ranging from 0 to 5 wt%, the oscillatory moduli of PE slightly increased with CF content. Transient shear flow measurements showed that the steady shear viscosity and first normal stress difference of PE also slightly increased with the addition of CF. Conversely, the strain hardening behaviors of PE were suppressed by CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…It is important to note that the surface of the extrudates remained smooth and rheological defects were absent in the range of shear rates applied. As observed for other polymer composites containing different types of fillers , addition of graphite nanoplates decreased extrudate‐swell. The nanocomposite containing F‐GnP exhibits a slightly higher elasticity than that with GnP.…”
Section: Resultssupporting
confidence: 67%
“…It is important to note that the surface of the extrudates remained smooth and rheological defects were absent in the range of shear rates applied. As observed for other polymer composites containing different types of fillers , addition of graphite nanoplates decreased extrudate‐swell. The nanocomposite containing F‐GnP exhibits a slightly higher elasticity than that with GnP.…”
Section: Resultssupporting
confidence: 67%
“…In to correct the apparent shear rate and apparent shear stress using the Rabinowitch and Bagley equations, respectively. However, we analyzed the extrusion behavior of these samples based on the uncorrected data, because the correction coefficient is almost independent of the fillers in highly dispersed filler system shown in our previous reports [8,9]. As shown in Fig.…”
Section: Measurementsmentioning
confidence: 99%
“…It is relatively easy to understand the origin of reduction in swell in composites having high entanglement and/or large contact among concentrated rigid fillers, because the elastic properties of polymers are suppressed due to formation of network structure of rigid fillers. On the other hand, the reduction in swell in high dispersion system is reported [8,9]. The addition of a small amount of rigid fillers to polymer is a useful method for controlling swell of molten polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work attempted to irradiate HDPE-based CFRTPs by an electron-beam to enhance their mechanical properties [ 20 ]. Generally, with HDPE, it is difficult to obtain satisfactory mechanical properties of HDPE-based CFRTP because HDPE has poor flow properties, which limits infiltration into the spaces between fibers, and has poor interfacial interaction with CF due to the non-polarity of HDPE [ 21 , 22 ]. However, we found that the tensile strength of the irradiated HDPE-based CFRTP was enhanced by simply increasing the absorbed dose.…”
Section: Introductionmentioning
confidence: 99%